Management of methylmalonic acidemia (MMA) with N‐carbamylglutamate: A case report from Italy. Issue 1 (4th November 2022) - Tubili, Flavia; Pochiero, Francesca; Curcio, Maria Rosaria; Procopio, Elena
Abstract: Background: Methylmalonic acidemia (MMA) is an inborn error of metabolism whose optimal management, especially in the long‐term remains to be established. Methods: We describe the case of a child with MMA mut 0 who was in a cycle of episodes of decompensation and hospitalization when we started to use carglumic acid (CA), a well‐known adjunctive therapy to standard care for the treatment of acute hyperammonemia due to MMA. Results: Using the lowest effective therapeutic dose of CA and adjusting the patient's diet with caloric and protein intake adequate for her age and pathology, we managed to keep ammonium levels within the normal range, and to ensure a normal growth pattern. Conclusion: The present case adds further confirmation of the long‐term management of MMA using CA, focusing on the long duration of follow up and on the use of a lower dose of CA in real life settings. Abstract : We present the case report of a patient with frequently decompensated methylmalonic acidemia (MMA) who was successfully treated with carglumic acid (Carbaglu®, CA). The efficacy and safety of long‐term CA in the management of MMA have been confirmed in a prospective, randomized controlled trial and our report provides additional real‐world evidence on the ability of CA to improve the quality of life of patients with this rare disease.